The bacterial microbiome of symbiotic and menthol-bleached polyps of long-term aquarium-reared Galaxea fascicularis - Puntin, Giulia; Wong, Jane C. Y.; Röthig, Till; Baker, David M.; Sweet, Michael; Ziegler, Maren (Peer Community Journal)

(untitled)
Coral reefs support the livelihood of half a billion people but are at high risk of collapse due to the vulnerability of corals to climate change and local anthropogenic stressors. While understanding coral functioning is essential to guide conservation efforts, research is challenged by the complex nature of corals. They exist as metaorganisms (holobionts), constituted by the association between the (coral) animal host, its obligate endosymbiotic algae (Symbiodiniaceae), and other microorganisms comprising bacteria, viruses, archaea, fungi and other protists. Researchers therefore increasingly turn to model organisms to unravel holobiont complexity, dynamics, and how these determine the health and fitness of corals. The coral Galaxea fascicularis is an emerging model organism for coral symbiosis research with demonstrated suitability to aquarium rearing and reproduction, and to manipulation of the host-Symbiodiniaceae symbiosis. However, little is known about the response of the G. fascicularis microbiome to menthol bleaching—the experimental removal of the Symbiodiniaceae which represents the first step in coral-algal symbiosis manipulation. For this, we characterized the bacterial microbiome of symbiotic and menthol-bleached G. fascicularis originating from the Red Sea and South China Sea (Hong Kong) that were long-term aquarium-reared in separate facilities. We found that the coral-associated microbiomes were composed of relatively few bacterial taxa (10-78 ASVs). Symbiotic polyps (clonal replicates) from the same colony had similar microbiomes, which were distinct from those of other colonies despite co-culturing in shared aquaria. A pattern of seemingly differential response of the bacterial microbiome to menthol bleaching between the two facilities emerged, warranting further investigation into the role of rearing conditions. Nevertheless, the changes in community composition overall appeared to be stochastic suggesting a dysbiotic state. Considering the importance of bleaching treatment of captive corals for symbiosis research, our results—although preliminary—contribute fundamental knowledge for the development of the Galaxea model for coral symbiosis research.